2021
DOI: 10.29350/qjps.2021.26.4.1408
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Extract Role Against L-Thyroxine Effects On Thyroid Gland And Lipid Profile

Abstract: The aim of the current study is identify role grape seed extract on thyroid gland tissues, hormones and lipid profile disorders induced by L-Thyroxine by used dose 20 mg/kg. The experience including 40 male rats randomly divided into five groups each group consist of 8 animals,  grape seed extract dose 150mg/kg  daily for 30-day. Results showed that the animals treated with L-Thyroxine had significant increase(P<0.05) in  thyroid hormones concentration  and dencrease TSH hormone compared with their no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The findings of the present study are consistent with those of Shattnan et al (2017) who investigated the effects of carbimazoleinduced hypothyroidism on the thyroid gland, lipid profile, and protective effects of grape seed. Their findings revealed pronounced necrosis in the follicular cells and vacuolations of the colloid, which was present in small amounts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are consistent with those of Shattnan et al (2017) who investigated the effects of carbimazoleinduced hypothyroidism on the thyroid gland, lipid profile, and protective effects of grape seed. Their findings revealed pronounced necrosis in the follicular cells and vacuolations of the colloid, which was present in small amounts.…”
Section: Discussionsupporting
confidence: 92%
“…A bi-lobular endocrine gland, the thyroid is situated in the lower neck. It is a butterflyshaped organ that is located below the larynx on both sides of the trachea (Shattnan et al, 2017). The structure and functioning component of the thyroid gland is the thyroid follicle.…”
mentioning
confidence: 99%
“…As for the improvement in the totals treated with Omega-3 compared to T1group, it is due to the content of omega-3 unsaturated fatty acids, which are known for their regulatory properties of various body functions, they are classified among the most important anti-inflammatory and powerful oxidants that work to remove free radicals directly or indirectly by activating antioxidants such as GSH, CAT and SOD [24], where (EPA) is one of the most important fatty acids forming Omega-3, which makes up 18% of it, so it affects the level of thyroid hormones in two main directions, the first is the regulation of nerve signalling pathways by affecting the membrane lipids of thyroid cells, which contributes to increasing the sensitivity of TSH receptors as a result of the improvement in phospholipids of cell membranes on the one hand and the rapid and direct modification of the gene transcription process, which effectively contributes to reducing the level of T 3 , T 4 hormones inside and outside the gland thyroiditis [25], and the improvement in the level of (TSH) is attributed to the effect of Omega-3 in enhancing the immune response and reducing inflammation, as it works to increase the stability of cell membranes and thus regulate the function of the immune system and prevent excessive inflammatory reactions, which is reflected positively on the regulation of the functions of the glands and the secretion of hormones, including the TSH hormone. Table (1).…”
Section: Results and Discussion The Level Of Thyroid Hormones (T4 T3)...mentioning
confidence: 99%
“…The drug propylthiouracil at a concentration of (15 mg/kg) of body weight was used in the treatment of hyperthyroidism in this study to manufacture a drug nano-loaded on zinc oxide, as the intercalation of the drug between zinc oxide layers was carried out by direct ion exchange. This technique showed that propylthiouracil gave spectra indicating the success of the intercalation process, which was used in the subsequent stages of the study Figure (1,2). The surface of ZnO particles loaded with the drug in its solid state was tested using X-ray diffraction, to find out some of its structural properties such as crystal phase, crystal size and its purity can also be estimated.…”
Section: Nanoparticle Assay Of Propylthiouracil Zinc Oxide Nanopartic...mentioning
confidence: 99%
See 1 more Smart Citation